Factors predicting help seeking for mental illness among college students. (4th May 2021) - Kosyluk, Kristin A.; Conner, Kyaien O.; Al-Khouja, Maya; Bink, Andrea; Buchholz, Blythe; Ellefson, Sarah; Fokuo, Konadu; Goldberg, David; Kraus, Dana; Leon, Adeline; Powell, Karina; Schmidt, Annie; et al.
Abstract: Background: Evidence supports the contribution of various stigma-related constructs to help-seeking. These constructs have yet to be tested in a single model among college students, a group highly affected by mental illness. Aims: Using data from 153 college students, this study examines factors contributing to help seeking for mental illness. Method: Using path analysis, the current study evaluated a model of the relationship between level of familiarity, personal stigma, desired social distance, label avoidance, attitudes towards treatment seeking and intentions to seek treatment. Results: Findings support a model of help-seeking describing the relationship between familiarity with mental illness, personal stigma, social distance, label avoidance, attitudes and intentions to seek treatment. Conclusions: Findings suggest label avoidance, attitudes towards treatment seeking and intentions to seek treatment might be augmented through interventions aimed at increasing college students' levels of familiarity, or intimate contact, with individuals with mental illness. Additional implications for practice and further research are addressed.